Metal-Air Batteries—A Review - Olabi, Abdul Ghani; Sayed, Enas Taha; Wilberforce, Tabbi; Jamal, Aisha; Alami, Abdul Hai; Elsaid, Khaled; Rahman, Shek Mohammod Atiqure; Shah, Sheikh Khaleduzzaman; Abdelkareem, Mohammad Ali (Energies (Basel), 2021)
Metal–air batteries are a promising technology that could be used in several applications, from portable devices to large-scale energy storage applications. This work is a comprehensive review of the recent progress made in metal-air batteries MABs. It covers the theoretical considerations and mechanisms of MABs, electrochemical performance, and the progress made in the development of different structures of MABs. The operational concepts and recent developments in MABs are thoroughly discussed, with a particular focus on innovative materials design and cell structures. The classical research on traditional MABs was chosen and contrasted with metal–air flow systems, demonstrating the merits associated with the latter in terms of achieving higher energy density and efficiency, along with stability. Furthermore, the recent applications of MABs were discussed. Finally, a broad overview of challenges/opportunities and potential directions for commercializing this technology is carefully discussed. The primary focus of this investigation is to present a concise summary and to establish future directions in the development of MABs from traditional static to advanced flow technologies. A systematic analysis of this subject from a material and chemistry standpoint is presented as well.